An investigation of exciton behavior in type-II self-assembled GaSb/GaAs quantum dots. (18th December 2015) - Qiu, Feng; Qiu, Weiyang; Li, Yulian; Wang, Xingjun; Zhang, Yun; Zhou, Xiaohao; Lv, Yingfei; Sun, Yan; Deng, Huiyong; Hu, Shuhong; Dai, Ning; Wang, Chong; et al.
Abstract: We report the investigation of exciton dynamics in type-II self-assembled GaSb/GaAs quantum dots. The GaSb/GaAs quantum dots (QDs) were grown using a modified liquid phase epitaxy technique. Statistical size distributions of the uncapped QDs were investigated experimentally by field-emission scanning electron microscopy (SEM) and atomic force microscopy (AFM), and theoretically by an eight-band k  ·  p calculation, which demonstrated a dissolution effect. Furthermore, the low-temperature luminescence spectra of type-II GaSb/GaAs QDs with a thick capping layer exhibit well-resolved emission bands and LO-phonon-assisted transitions in the GaSb wetting layer. However, the luminescence lines quench at temperatures above 250 K, which is attributed to the weak quantum confinement of electrons participating in indirect exciton recombination. It was demonstrated that the room temperature stability of the excitons in type-II GaSb/GaAs QDs could be achieved by growing thin a capping layer, which provides strong quantum confinement in the conduction band and enhances the electron–hole Coulomb interaction, stabilizing the excitons.